2001
DOI: 10.1021/es000230d
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of U.K. Salt Marsh Sediment Contaminant Data with Reference to the Significance of PCB Contamination

Abstract: A data set acquired to establish an inventory of pollutants in salt marsh sediments has been evaluated using two numerical techniques, principal component analysis and discriminant analysis. Results indicate that sites proximate to the River Thames exhibit a greater degree of contamination, and numerical analysis supports the hypothesis that the river has been the major source of contaminants to the region. The presence of the contaminants within salt marsh sediments may be of concern due to changes in flood d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The Varimax rotation was carried out to maximize the variance to facilitate the interpretation of the results. However, as observed by Scrimshaw et al (41), the unrotated and rotated PCs gave broadly similar results. Therefore, the former was compared with the GAIA results.…”
Section: Resultssupporting
confidence: 85%
“…The Varimax rotation was carried out to maximize the variance to facilitate the interpretation of the results. However, as observed by Scrimshaw et al (41), the unrotated and rotated PCs gave broadly similar results. Therefore, the former was compared with the GAIA results.…”
Section: Resultssupporting
confidence: 85%
“…The most relevant data that exists is only for PCB as Aroclor-1248 in salt marsh sediment of Two Tree Island in the Thames estuary where a mean value of 34.4 µg/kg was reported (1990)(1991)(1992)(1993)(1994)(1995) (Scrimshaw and Lester, 2001). Much lower values have been reported for the same congeners in the River Willamette (located in northwestern Oregon, US) and Lake Thun (situated in the Bernese Oberland, Swizerland) (Bogdal et al, 2010;Hope, 2008) but these are both very rural areas (>90%).…”
Section: Comparison Of Predicted Values Against Observed Datamentioning
confidence: 99%
“…The burden of PCBs in the sediments has the potential to be bioavailable for Thames fish (OSPAR, 2009b). Although limited sediment data is available for non-tidal section of Thames, a recent study suggested that the sediment concentrations of PCBs in the Thames estuary observed in 2011 significantly exceeded the Ecotoxicological Assessment Criteria derived by the Oslo and Paris Convention (OSPAR) (Nicolaus et al, 2015;Scrimshaw and Lester, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…The ΣPCB(tri-hepta) concentrations of the Delmarva are significantly lower compared to that from a study of salt marsh surface sediments of Barnegat Bay-Little Egg Harbor Estuary, New Jersey, where it ranged from 4 to 50 µg/kg with a mean of 21µg/kg (Vane et al, 2008). Higher values have been reported in surface sediments taken from the mudflats of the Mullica River, New Jersey, that has been relatively unaffected by industrial and urban influences (Iannuzzi et al, 2005) where total PCB concentrations were 25-46 μg/kg (mean of 36 μg/kg).This can be explained by the sorption of PCBs to clay and or natural organic matter (Fox et al, 2001;Scrimshaw and Lester, 2001). Generally as %TOC of sediments increase so does its capacity for PCB sorption.…”
mentioning
confidence: 95%
“…Estuary sediments and salt marshes on the east coast of the USA are potentially important sinks for POPs due to preferential adsorption of pollutants to organic matter (Fox et al, 2001;Scrimshaw and Lester, 2001). In this study we examine the sediments from an urban (the Delaware River Estuary) and rural (Delmarva Peninsula) setting to:…”
mentioning
confidence: 99%